2019
DOI: 10.12968/bjon.2019.28.6.s38
|View full text |Cite
|
Sign up to set email alerts
|

A nursing metaparadigm perspective of diabetic foot ulcer care

Abstract: Diabetic foot ulcers (DFUs) are a serious complication of diabetes that impact on the patient, their social environment, overall health, and on nursing practice. Nursing scholars have integrated theories on practice to overcome these problems, but a lack of agreement in the available literature acts as a barrier to implementing these in practice. For that reason, using a nursing metaparadigm as a theoretical framework would assist nurses in managing care purposefully and proactively, thus possibly improving ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 110 publications
0
3
0
1
Order By: Relevance
“…DFU is one of the most common complications of diabetes, causing not only burdens for patients but also posing challenges for overall health, nursing practices, and the social environment. 32 Patients with diabetes often experience weakened immune systems, and when coupled with the vulnerability of the feet as one of the body's vital organs, infections can exacerbate inflammation and ultimately play a role in the onset of DFU. 33 This study, from an immunological perspective, identified GSTM5 as a potential key target for DFU using machine learning and Based on the conclusions of this study, GSTM5 is significantly underexpressed in DFU tissues, suggesting that it may be a potential protective factor in DFU patients.…”
Section: Discussionmentioning
confidence: 99%
“…DFU is one of the most common complications of diabetes, causing not only burdens for patients but also posing challenges for overall health, nursing practices, and the social environment. 32 Patients with diabetes often experience weakened immune systems, and when coupled with the vulnerability of the feet as one of the body's vital organs, infections can exacerbate inflammation and ultimately play a role in the onset of DFU. 33 This study, from an immunological perspective, identified GSTM5 as a potential key target for DFU using machine learning and Based on the conclusions of this study, GSTM5 is significantly underexpressed in DFU tissues, suggesting that it may be a potential protective factor in DFU patients.…”
Section: Discussionmentioning
confidence: 99%
“…This is done with the participation of health system staff consisting of physicians and nurses. [ 19 ] Bentley and colleagues acknowledged that diabetic foot ulcers require specific management and. Diabetic foot ulcers require accurate and rapid assessment, diagnosis, treatment, and long-term follow-up in order to maintain the foot.…”
Section: Discussionmentioning
confidence: 99%
“…Embora esse estudo não tenha apresentado um grupo controle, os resultados demonstraram efeitos positivos quanto à redução da área da úlcera no grupo agudo (15) . paciente tomar decisões sobre seu próprio tratamento (16) .…”
Section: Em Estudo Descritivo Realizado Nounclassified